2019
DOI: 10.1080/0284186x.2019.1581372
|View full text |Cite
|
Sign up to set email alerts
|

Screening individuals’ experiences of colonoscopy and colon capsule endoscopy; a mixed methods study

Abstract: Background: The standard investigation in colorectal cancer screening (optical colonoscopy [OC]) has a less invasive alternative with the colon capsule endoscopy (CCE). The experiences of screening individuals are needed to support a decision aid (DA) and to provide a patient view in future health technology assessments (HTA). We aimed to explore the experiences of CCE at home and OC in an outpatient clinic by screening participants who experienced both investigations on the same bowel preparation. Methods: In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
48
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 37 publications
(50 citation statements)
references
References 28 publications
2
48
0
Order By: Relevance
“…Surprisingly, they also observed that only 85.7 % of the CCE patients were willing to undergo the same test again, compared with 93.6 % and 96.1 % for colonoscopy and CT-colonography patients, respectively. We investigated this in a previous publication and found support for this statement [4]. In addition to acceptability, logistics is another concern.…”
Section: Discussionmentioning
confidence: 78%
“…Surprisingly, they also observed that only 85.7 % of the CCE patients were willing to undergo the same test again, compared with 93.6 % and 96.1 % for colonoscopy and CT-colonography patients, respectively. We investigated this in a previous publication and found support for this statement [4]. In addition to acceptability, logistics is another concern.…”
Section: Discussionmentioning
confidence: 78%
“…This is the first time that patient perspectives across three GI procedures have been explored using in-depth, qualitative methods. While some qualitative literature exists, this tends to focus on specific populations (eg, Barrett’s oesophagus surveillance, colorectal cancer screening25 26) or specific aspects of experience (eg, comfort during colonoscopy versus colon capsule endoscopy26 27). Furthermore, where more than one modality has been explored findings have been analysed and described separately 26.…”
Section: Discussionmentioning
confidence: 99%
“…In another study [70] where CCE was offered to patients who were unwilling to undergo optical colonoscopy after a positive FIT, a participation rate of 5 % was found. Although contradictory data on patient preference are available, recent data from a large Danish series of screening individuals suggests CCE was associated with less discomfort than optical colonoscopy and may be preferable to some individuals [71].…”
Section: Cce and Screening For Colorectal Cancer: Participationmentioning
confidence: 99%